Treated wastewater application in agriculture: potential assessment in the State of Santa Catarina/Brazil (Sustainability in Debate, 2023)
This study aimed to evaluate the potential of using treated wastewater in the irrigation of 7 crops produced in the State of Santa Catarina by assessing the current demand for irrigation water in the study area and the future production of treated wastewater. Food production data were collected from the most significant public agricultural institution in the study area to calculate their blue water footprint, given the amount of food harvested. Future wastewater production data were gathered from official reports which present the sanitation plans to be performed by 2035. Geographic Information System tools and risk assessment approaches were used to present and discuss results from quantitative and qualitative perspectives. Results show that the amount of wastewater to be produced in 2035 could not only supply the current irrigation water demand for the selected crops but also allow agriculture to expand without consuming more potable water.